Pulp obtaining from corn stalks - Barbash, Valerii; Trembus, Irina; Nagorna, Julia (Publishing House of Lviv Polytechnic National University, 2012)
The influence of basic technological parameters of the organosolvent delignification of corn stalks process on the pulps quality has been investigated. The adequate regression equations of the process of obtaining pulps using the method of full factorial experiment have been obtained. The optimal values of technological parameters of organosolvent delignification of corn stalks have been calculated. The possibility of bleaching the organosolvent pulp obtained from corn stalks by hydrogen peroxide without the use of chlorine compounds to whitenees more than 80 % has been proved by the experiments. Досліджено вплив основних технологічних параметрів процесу органосольвентної делігніфікації стебел кукурузи на показники якості волокнистих напівфабрикатів. Отримано адекватні рівняння регресії процесу одержання волокнистих напівфабрикатів з використанням методу повного факторного експерименту, які використано для розрахунку оптимальних значень технологічних параметрів. Експериментально доведено можливість вибілювання органосольвентної целюлози із стебел кукурудзи пероксидом водню до білості більше 80% без використання сполук хлору.
Одержання волокнистих напівфабрикатів із стебел кукурудзи
Keywords: organosolvent delignification; corn stalk; pulp; bleaching; a regression equation; optimization; органосольвентна делігніфікація; стебло кукурудзи; целюлоза; волокнистий напівфабрикат; вибілювання; рівняння регресії; оптимізація